Bourdieu's Field Theory, as a Theoretical Framework for Analyzing the Process of Degree Completion in Graduate Education - Rosalba Angélica Sánchez Dromundo (Universidad Autónoma de Baja California, 2007)
The article presents a scheme for the analysis of degree completion. This scheme is the result of research on the graduation of students with a Master's degree in Pedagogy at the Universidad Nacional Autónoma de México in 2003. Theoretical support comes from two sources: Arredondo and Sánchez Puentes (2000 and 2004), who affirm that graduation is a formative process that initiates with incorporation in the program and culminates with degree conferral; and Bourdieu, who helps to understand the factors that affect integration through concepts like field, cultural capital and habitus. The empirical data comes from interviews with students, graduates, advisors, and the graduate program staff. The article emphasizes the way in which the cultural capital and habitus affect education and impede graduation, and exposes some of the mechanisms of exclusion in the educational processes.